The Specifics of Students' Self-Control - Kholmurotovna , Avezova (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
In the life and work of every person, the problem of regulating activity in the changing conditions of the surrounding existence is of great importance. According to modern views, the meaningful description of the entire psyche of a person is the self-regulation of goal-oriented activity, the ability to "create oneself" that makes a person a free and conscious subject in his life and activities. In the processes of self-management, the unity of the separate stages, sides, possibilities, functions, processes, abilities, etc. of the psyche in all its wealth is realized. In general, the concept of "self-management" has an interdisciplinary character. Self-regulation is a systemic process that provides flexibility in all periods of life and activity, adequate variability to the conditions. In the works of many authors, there are attempts to distinguish the psychological aspect of self-regulation. It happened in the context of the problem of the general composition and dynamics of human activity, which is closely related to such directions as self-determination, responsibility and decision-making.